2005
DOI: 10.1108/13660750510594864
|View full text |Cite
|
Sign up to set email alerts
|

Access and utilization of health services by British Columbia's rural Aboriginal population

Abstract: PurposeTo provide a picture of the access and use of health services by Aboriginal British Columbians living in both reserve and off‐reserve communities.Design/methodology/approachThis project represents a collaborative effort between the University of British Columbia and multiple Aboriginal community partners. Between June and November 2003, 267 face‐to‐face interviews were conducted with Aboriginal persons in seven rural community organizations across the province.FindingsThis paper reports on the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…20 Participants were very clear in their call for greater support for traditional health care practices through policies to ensure that traditional health care practices are recognized, increased funding for culturally appropriate interventions, and continued research. These findings are consistent with similar calls to action for culturally appropriate health care 24,26 and policy. 19,21 Greenwood and de Leeuw note, "Effective programs are characterized by vision and leadership, holism, active community participation, strengths-based orientation, and reinvigoration and revitalization of Aboriginal cultures aimed at realizing self-determination" (p. 383).…”
Section: Discussionsupporting
confidence: 78%
“…20 Participants were very clear in their call for greater support for traditional health care practices through policies to ensure that traditional health care practices are recognized, increased funding for culturally appropriate interventions, and continued research. These findings are consistent with similar calls to action for culturally appropriate health care 24,26 and policy. 19,21 Greenwood and de Leeuw note, "Effective programs are characterized by vision and leadership, holism, active community participation, strengths-based orientation, and reinvigoration and revitalization of Aboriginal cultures aimed at realizing self-determination" (p. 383).…”
Section: Discussionsupporting
confidence: 78%
“…We offer these GIS techniques as an alternative to the current practice of arbitrarily locating new facilities on the basis of perceptions about patient demand. These findings may be applicable when planning the locations for future healthcare services for other chronic diseases requiring regular medical follow-up such as diabetes, cardiovascular disease, cancer, and chronic respiratory illnesses (13)(14)(15)(16)(17)(18)20,25).…”
Section: Discussionmentioning
confidence: 99%
“…Increased travel time to receive specialty care for such illnesses is a potentially reversible determinant of adverse outcomes, and several studies have shown that increased distance between the patient's residence and the closest relevant medical specialist is associated with adverse outcomes (9 -12). Even within a relatively small geographic area, shorter distances to healthcare services and availability of such services at the nearest center were strongly related to increased utilization of healthcare and better outcomes (12)(13)(14)(15)(16)(17)(18)(19)(20). Given that geography is a potentially reversible barrier to accessing healthcare services, careful planning to optimize the placement of future healthcare facilities with the goal of enhancing service and improving healthcare outcomes for remote dwellers is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have also examined the race and ethnic disparities in health care in developing countries such as the United States (Jones, Trivedi & Ayanian, 2010:337;Jimenez, Cook Bartels & Alegría, 2013;Palmer, Geiger, Felder, Lu, Case & Weaver, 2013), New Zealand (Rumball-Smith, Sarfati, Hider & Blakely, 2013 and Canada (Wardman, Clement, & Quantz, 2005) as well as various developing countries such as India, Chile, Argentina, Brazil, Costa Rica, Ghana, and Tanzania (Balarajan, Selvaraj, Subramanian, 2011;Marmot, Allen, Bell, Goldblatt, 2012;Mills, Ataguba, Akazili, Borghi, Garshong, Makawia, Mtei, Harris, Macha, Meheus & McIntyre 2012). However, far less research on the racial disparities with regards to tangible service delivery in public health care has been conducted in emerging markets, such as South Africa.…”
Section: Introductionmentioning
confidence: 99%